Advancing Ocean Acidification Biology Using Durafet® pH Electrodes - Kapsenberg, Lydia; Bockmon, Emily E.; Bresnahan, Philip J.; Kroeker, Kristy J.; Gattuso, Jean-Pierre; Martz, Todd R. (Frontiers in Marine Science, 2017)
Research assessing the biological impacts of global ocean change often requires a burdensome characterization of seawater carbonate chemistry. For laboratory-based ocean acidification research, this impedes the scope of experimental design. Honeywell Durafet® III pH electrodes provide precise and continuous seawater pH measurements. In addition to use in oceanographic sensor packages, Durafets can also be used in the laboratory to track and control seawater treatments via Honeywell Universal Dual Analyzers (UDAs). Here we provide performance data, instructions, and step-by-step recommendations for use of multiple UDA-Durafets. Durafet pH measurements were within ±0.005 units pHT of spectrophotometric measurements and agreement among eight Durafets was better than ±0.005 units pHT. These results indicate equal performance to Durafets in oceanographic sensor packages, but methods for calibration and quality control differ. Use of UDA-Durafets vastly improves time-course documentation of experimental conditions and reduces person-hours dedicated to this activity. Due to the versatility of integrating Durafets in laboratory seawater systems, this technology opens the door to advance the scale of questions that the ocean acidification research community aims to address.